Adrenopause – does it really exist? - Papierska, Lucyna (Menopause Review/Przegląd Menopauzalny, 2017)
In ageing human adrenal glands there occur some morphological changes which result in alterations of their cortex endocrine function. Glucocorticoid-excreting cells in the zona glomerulosa live longer than androgen-producing cells in the zona reticularis, which undergo significant apoptosis. Therefore, in elderly humans cortisol levels are normal (significantly higher than at young age), while adrenal androgen concentrations decline with ageing. Function of the zona glomerulosa is affected by the adrenal status, circulatory system condition, efficiency of the kidneys and liver and medication. An important problem of ageing is the rising incidence of non-secreting, incidentally detected, benign adrenal tumors, called incidentalomas. They necessitate clear-sighted radiological and hormonal diagnosis.